Prospects for cloud technologies in higher education - S. I. Sokhina; Z. Z. Malinina; O. N. Shevchenko (Academy of Cognitive and Natural Sciences, 2013)
Interconnectedness and interdependence in today's world, due to information flows, unite all people into a single whole. Even in the distant past, when humans were few and the world was largely divided, the populations of particular regions and countries slowly but surely interacted, and at some point humanity separated from the rest of the biosphere and created its own environment. Now that human activity has taken on a planetary scale, the question of our interaction has become acute. Collective interaction, linked with all the information that has gone before, describes all processes of an economic, technological, cultural, social and biological nature. Collective interaction is based on the transmission and multiplication of generalized information. The collective experience of the interaction of all people is transmitted to the next generation and spreads out, synchronizing the development of humanity on our planet. When a population was cut off from the bulk of humanity for a long period of time, its development slowed down. Mankind has always evolved as a global system, where in a single information space an inherently common and effective interaction is realized. Powerful global information systems are emerging, such as the Internet, which materializes the collective consciousness of mankind. An international education system is taking shape.